2010
DOI: 10.1242/jeb.030601
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular performance of six species of field-acclimatized centrarchid sunfish during the parental care period

Abstract: SUMMARYParental care is an energetically costly period of the life history of many fish species characterized by extended high intensity activity. To date, there have been no studies that have investigated the cardiovascular correlates of extended parental care in fish. Using Doppler flow probes, the cardiovascular performance of six syntopic centrarchid fish species (N232) that provide sole, male parental care was examined across a range of water temperatures that encompass their reproductive periods (14-26°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…2). Interestingly, hematocrit often declines in breeding individuals providing energetically demanding parental care relative to non-breeding individuals across a wide range of vertebrate taxa (Williams et al 2004, Fair et al 2007, Hanson and Cooke 2009, Cooke et al 2010), although further work is needed to determine whether this is an adaptive reduction to facilitate increased energetic demands or a consequence of osmoregulatory adjustments to blood during reproduction (Williams et al 2004, Fair et al 2007, Wagner et al 2008, Williams 2012). Thus, hematocrit may play an important role in the life history of all vertebrates, and further experimental work may shed light on the functional significance of this trait in mediating long-term consequences for survival and reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…2). Interestingly, hematocrit often declines in breeding individuals providing energetically demanding parental care relative to non-breeding individuals across a wide range of vertebrate taxa (Williams et al 2004, Fair et al 2007, Hanson and Cooke 2009, Cooke et al 2010), although further work is needed to determine whether this is an adaptive reduction to facilitate increased energetic demands or a consequence of osmoregulatory adjustments to blood during reproduction (Williams et al 2004, Fair et al 2007, Wagner et al 2008, Williams 2012). Thus, hematocrit may play an important role in the life history of all vertebrates, and further experimental work may shed light on the functional significance of this trait in mediating long-term consequences for survival and reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Hematocrit varies markedly in birds, with some of the highest values observed in migratory birds (Piersma et al 1996), but declining after breeding to lows during the postnuptial molt (Hõrak et al 1998, Davey et al 2000, Williams 2012). Declines during the breeding season have been documented in a number of birds (and in many other taxa as well), the ecological relevance of which has been previously underappreciated (Williams et al 2004, Fair et al 2007, Hanson & Cooke 2009, Cooke et al 2010, Williams 2012, Bowers et al 2014. As nearly all life-history functions are intimately linked to oxygen-carrying capacity, low capacity or low hematocrit can have deleterious effects on fitness in wild animals.…”
Section: Hematocrit As a Driver Of Foraging Behavior And Habitat Selementioning
confidence: 99%
“…A marginally non-significant positive relationship between R%fH and parental male aggression level was detected (Figure 2.6), however this did not affect parental care behaviours, specifically nest defending, nest tending and nest guarding investment. Hence, our results partially support the hypothesis: although fH is related to an individual's aggression level, the lack of relationship between fH and parental care behaviours suggests that fH alone does not appear to be directly related to parental care investment in smallmouth bass.The recorded fH conforms with the rates reported in previous literature(Schreer et al 2001 (16°C = 34.5 beats min -1 ±2.7 beats min -1 and 20°C = 52.8 beats min -1 ± 2.5 beats min -1 for routine fH and scope for fH ranging between 1.8 and 2.6 fold); Cooke 2004 (21°C = ~49 beats min -1 for routine);Cooke et al 2010 (21°C= ~50 beats min -1 for routine);Cooke et al 2004b (in largemouth bass (Micropterus salmoides) 17°C = ~48 beats min -1 , 21°C = ~50 beats min -1 , and 25°C = ~ 60 beats min -1 for routine fH; 17°C = ~80 beats min -1 , 21°C = ~90 beats min -1 , and 25°C = ~ 120 beats min -1 for max fH), measured within the same temperature range (16-23°C).…”
supporting
confidence: 90%
“…The apparent relationships between cardiovascular performance and metabolism, and physiological capacity for exercise and parental care behaviour has motivated the hypothesis that fitness and fitness-related behaviours are strongly influenced by cardiovascular performance (Franklin and Davie 1992;Cooke 2004;Farrell et al 2008;Cooke et al 2010). Previous research has shown that smallmouth bass (and other centrarchid species) undergo behavioural and physiological adaptations, including modulating fH to enhance reproductive performance .…”
Section: Introductionmentioning
confidence: 99%